Perceived Service Fairness Dan Revisit Intention Galatama: Peran Mediasi Customer Satisfaction - Theodora Amelia; Rudiyanto; Ferdian Arie Bowo (Journal of Creative Power and Ambition (JCPA), 2026)
The challenge of decreasing visitor volume at Galatama Lele Oiko Fishing, East Jakarta, reflects the problem of meeting participant expectations amidst the intense competition for special interest recreation. This study was conducted with the aim of empirically testing the effect of Perceived Service Fairness mediated by Customer Satisfaction on Revisit Intention among Galatama Lele Oiko Fishing, East Jakarta participants. The quantitative approach in this study was through the distribution of closed questionnaire instruments to respondents as a sample population. The study population included all participants who actively fished at Galatama Lele Oiko Fishing, East Jakarta, between August 2025 and January 2026. Based on a non-probability sampling technique with a purposive sampling method, a sample of 161 respondents was collected, exceeding the minimum threshold of the Slovin formula of 99.04. The data analysis stage was carried out using the Structural Equation Modeling (SEM) method with the help of SmartPLS 4.0. The findings from the hypothesis testing through bootstrapping proved that Perceived Service Fairness mediated by Customer Satisfaction had a positive and significant impact on Revisit Intention. Based on the Adjusted R-Square value, the combination of Perceived Service Fairness and Customer Satisfaction simultaneously has a moderate ability to encourage Revisit Intention of 58.9% with an external model factor of 79.2%, although the Perceived Service Fairness variable partially has a weak direct influence in explaining Customer Satisfaction of 20.8% with an external model factor of 41.1%.